2018
DOI: 10.1002/stc.2180
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on seismic control of cable-stayed bridges using shape memory alloy self-centering dampers

Abstract: This paper presents the experimental investigations of a novel self-centering damper (SCD) for controlling seismic responses of cable-stayed bridges. The damper is fabricated employing the super-elasticity effect and energy dissipation characteristics of shape memory alloy wires. Within super-elastic range, a damping force model is derived and verified based on the constitutive model of shape memory alloy wires. One reduced-scale cable-stayed bridge model is designed to investigate its seismic control performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The significant hysteresis in the stress-strain relationship of SMAs makes them an ideal candidate for implementation in passive vibration control [73][74][75][76]. Applications include control of stay cables [77,78], isolation bearings [79][80][81][82][83][84], and frame braces [85,86]. Due to its high damping capacity, SMA is an ideal energy dissipating material in passive control.…”
Section: Pounding Tuned Mass Damper (Ptmd) and Energy Dissipating Matmentioning
confidence: 99%
“…The significant hysteresis in the stress-strain relationship of SMAs makes them an ideal candidate for implementation in passive vibration control [73][74][75][76]. Applications include control of stay cables [77,78], isolation bearings [79][80][81][82][83][84], and frame braces [85,86]. Due to its high damping capacity, SMA is an ideal energy dissipating material in passive control.…”
Section: Pounding Tuned Mass Damper (Ptmd) and Energy Dissipating Matmentioning
confidence: 99%
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, beam‐to‐column connections, base isolators, and bridges …”
Section: Introductionmentioning
confidence: 99%
“…Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, [14][15][16][17] beam-to-column connections, [18][19][20][21][22][23][24] base isolators, 25,26 and bridges. 27,28 Although the wire form of SMA has proven to be effective in providing energy dissipation and self-centring capability, there are still practical issues such as difficulty of gripping (especially when a large number of wires are to be included) and vulnerability to fracture at the gripping region due to local stress concentration. It is noticed that most of the existing prototype damping devices are small-scale ones, where the level of load resistance is generally inadequate for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with electrorheological fluid, magnetorheological fluid (MRF), and shape memory alloy, shear thickening fluid (STF) is another smart material with excellent performance given that the characteristics of STF depend on its shear strain rate. Under high strain rate loading, the apparent viscosity of the contact interface changes dramatically, even from liquid phase to solid phase .…”
Section: Introductionmentioning
confidence: 99%